Spatial distribution-based progression of spinal cord injury pathology: a key role for neuroimmune cells - Li, Jian; Zhai, Xiaolei; Yu, Chaochun (Frontiers in Immunology, 2025)
An external trauma, illness, or other pathological cause can harm the structure and function of the spinal cord, resulting in a significant neurological disorder known as spinal cord injury (SCI). In addition to impairing movement and sensory functions, spinal cord injury (SCI) triggers complex pathophysiological responses, with the spatial dynamics of immune cells playing a key role. The inflammatory response and subsequent healing processes following SCI are profoundly influenced by the spatial distribution and movement of immune cells. Despite significant advances in both scientific and clinical research, SCI therapy still faces several challenges. These challenges primarily stem from our limited understanding of the spatial dynamics of immune cell distribution and the processes that regulate their interactions within the microenvironment following injury. Therefore, a comprehensive investigation into the spatial dynamics of immune cells following SCI is essential to uncover their mechanisms in neuroinflammation and repair, and to develop novel therapeutic strategies.